Is There a Gender Imbalance in the Italian Labor Market? - Giuseppina Sacco; Pietro Sacco; Alfonso Zizza (European Scientific Journal, ESJ, 2021)
Women who decide to enter the labor market should, at least in theory, have access to any profession. Actually, it is something that does not always happen and their ambitions are relegated to few jobs (i.e., teachers, nurses, cashiers,) often linked to social stereotypes characterized by low wages, tasks that are inappropriate to their educational qualifications and of course with few career prospects. All that creates a gender imbalance of individuals in the labor market known as segregation. The objective of this paper is to focus on the aforementioned issue through a qualitative and quantitative survey based on the analysis of statistical indicators compared in two years (2009 and 2020), taking into account the social variations of the time span that elapses between the two years observed. The results show that gender employment segregation has been opposed over time, but not adequately resolved by concrete policies that can counter the phenomenon under consideration. Therefore, it is not enough to increase women's employment without pursuing a path of qualitative growth in women's work.